Role of Neutrophil Extracellular Traps in Hypertension and Their Impact on Target Organs - Fei Yu; Jianshu Chen; Xiaowei Zhang; Zhengke Ma; Jingtao Wang; Qiang Wu (The Journal of Clinical Hypertension)
ABSTRACT Hypertension is the predominant cause of cardiovascular diseases (CVDs) globally, and essential hypertension (EH) represents a significant public health challenge due to its multifactorial etiology involving complex interactions between genetic and environmental factors. However, the pathogenesis of EH is still unclear. Hypertension is a dysregulation in the renin–angiotensin–aldosterone system and sympathetic nervous system, both regulating saline homeostasis and cardiovascular function. However, current therapeutic interventions targeting these systems have limited efficacy in approximately 40% of cases, suggesting the involvement of alternative mechanisms. Inflammation is associated with the occurrence and progression of hypertension, but the underlying mechanism remains elusive, while chronic inflammation leads to tissue damage, fibrosis, and irreversible organ dysfunction. The development and maintenance of EH are caused by endothelial dysfunction, oxidative stress, and chronic inflammation. Neutrophils are involved in both acute and chronic inflammation since they represent the primary line of defense against inflammatory insults once recruited to the inflamed site where they remove harmful impurities. The process involving the formation of neutrophil extracellular traps (NETs) is called NETosis are involved in the pathogenesis and progression of CVDs, including coronary artery disease, acute myocardial infarction, peripheral arterial disease, heart failure, and atrial fibrillation. Recent investigations demonstrated that NETs facilitate the development of hypertension; however, the precise role of NETs in hypertension remains largely elusive. Therefore, this review aims to provide an overview of the current understanding regarding the involvement of NETosis in hypertension and explore the potential therapies targeting NETs for future interventions.